2011
DOI: 10.1093/annonc/mdq734
|View full text |Cite
|
Sign up to set email alerts
|

A phase I pharmacokinetic and pharmacodynamic study of AT7519, a cyclin-dependent kinase inhibitor in patients with refractory solid tumors

Abstract: AT7519 elicited clinical and PD activity resulting from CDK inhibition at doses below the appearance of DLT of QTc prolongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 14 publications
2
41
0
Order By: Relevance
“…This compound had lower potency against other CDKs tested (CDK3 and CDK7) and was inactive against all of the non-CDK kinases tested with the exception of GSK3 (IC 50 = 0.089 M). Phase I clinical trial was carried out in 28 patients with refractory solid tumors (Mahadevan et al 2011). Electrocardiogram showed a dose-dependent increase in QTc.…”
Section: Broad-range Inhibitorsmentioning
confidence: 99%
“…This compound had lower potency against other CDKs tested (CDK3 and CDK7) and was inactive against all of the non-CDK kinases tested with the exception of GSK3 (IC 50 = 0.089 M). Phase I clinical trial was carried out in 28 patients with refractory solid tumors (Mahadevan et al 2011). Electrocardiogram showed a dose-dependent increase in QTc.…”
Section: Broad-range Inhibitorsmentioning
confidence: 99%
“…Single AT7519 treatment of patients with advanced/metastatic solid tumors or refractory non-Hodgkin's lymphoma will provide data to applicable dose, pharmacokinetics, pharmacodynamics and side effects. First results of this study suggested evidence of clinical activity of AT7519, due to reduction of PCNA, a protein required for DNA replication, as a result of Cdk inhibition and an increase of apoptosis markers (Mahadevan et al, 2011). Mucositis, neutropenia, and reversible thrombocytopenia were identified as dose limiting toxicities.…”
Section: Cdk Inhibitors For Cancer Therapymentioning
confidence: 77%
“…Soluble CK18 fragments allowed detection of seliciclibinduced cell death in the blood of patients treated at doses above 800 mg/day. Another CDK inhibitor, namely AT7519, afforded stable disease for >6 months in four out of 28 patients and a prolonged partial response in one patient bearing solid tumors (Mahadevan et al, 2011). Inhibition of markers of CDK activity was observed across the dose range and manifested in antiproliferative activity.…”
Section: Targeted Chemotherapy and Changes In Circulating Ck18 And CCmentioning
confidence: 97%